Activation of MEK/ERK signaling contributes to the PACAP-induced increase in guinea pig cardiac neuron excitability - Tompkins, John D. (Am J Physiol Cell Physiol, 2016)
Pituitary adenylate cyclase (PAC)-activating polypeptide (PACAP) peptides (Adcyap1) signaling at the selective PAC1 receptor (Adcyap1r1) participate in multiple homeostatic and stress-related responses, yet the cellular mechanisms underlying PACAP actions remain to be completely elucidated. PACAP/PAC(1) receptor signaling increases excitability of neurons within the guinea pig cardiac ganglia, and as these neurons are readily accessible, this neuronal system is particularly amenable to study of PACAP modulation of ionic conductances. The present study investigated how PACAP activation of MEK/ERK signaling contributed to the peptide-induced increase in cardiac neuron excitability. Treatment with the MEK inhibitor PD 98059 blocked PACAP-stimulated phosphorylated ERK and, in parallel, suppressed the increase in cardiac neuron excitability. However, PD 98059 did not blunt the ability of PACAP to enhance two inward ionic currents, one flowing through hyperpolarization-activated nonselective cationic channels (I(h)) and another flowing through low-voltage-activated calcium channels (I(T)), which support the peptide-induced increase in excitability. Thus a PACAP- and MEK/ERK-sensitive, voltage-dependent conductance(s), in addition to I(h) and I(T), modulates neuronal excitability. Despite prior work implicating PACAP downregulation of the K(V)4.2 potassium channel in modulation of excitability in other cells, treatment with the K(V)4.2 current blocker 4-aminopyridine did not replicate the PACAP-induced increase in excitability in cardiac neurons. However, cardiac neurons express the ERK target, the Na(V)1.7 sodium channel, and treatment with the selective Na(V)1.7 channel inhibitor PF-04856264 decreased the PACAP modulation of excitability. From these results, PACAP/PAC1 activation of MEK/ERK signaling may phosphorylate the Na(V)1.7 channel, enhancing sodium currents near the threshold, an action contributing to repetitive firing of the cardiac neurons exposed to PACAP.